A single dose of lipopolysaccharide elicits autofluorescence in the mouse brain - Yang, Yanzhuo; Yu, Qingting; Li, Bin; Li, Shijia; Yang, Zuisu; Yuan, Falei; Liu, Zhongliang (Frontiers in Aging Neuroscience, 2023)
One hallmark of aging is autofluorescence (AF) in the brain. However, the underlying mechanism for inducing AF remains unknown. This study aims to determine the cause(s) of this phenomenon. The endogenous expression pattern of AF in mice was examined at differing ages. Intraperitoneal injection of a single dose of lipopolysaccharide (LPS) was performed to induce AF. Copper sulfate was applied to remove AF to allow for further immunofluorescence staining. AF appeared in the mouse brain as early as three months of age. In the cortex, AF occurs in the lysosomes of microglia, astrocytes, endothelial cells, and oligodendrocyte lineage cells and its prevalence increases with age. Interestingly, AF never occurs in the pericytes of young or aged brains. LPS administration resulted in a rapid and marked induction of brain AF, similar to the normal aging process. Finally, age-related and induced AF can be eliminated by low concentrations of copper sulfate solution. This pre-treatment is safe for aging and lineage tracing studies. These findings depict that AF in the brain could be associated with the innate immune response against Gram-negative bacteria infection.